BRANDING DESA WISATA TOLERANSI BUWUN SEJATI MELALUI BERITA ONLINE MANDALIKA POST - Rieka Yulita Widaswara; Sayu Kadek Jelantik (Widya Sandhi Jurnal Kajian Agama Sosial dan Budaya, 2022)
This study aims to examine the potential of Buwun Sejati tourism village in an effort to brand tourism villages to attract tourist visits. Buwun Sejati Village besides having beautiful natural potential also has its own potential, namely the life of the Buwun Sejati village community which is thick with the value of tolerance even though they live side by side with religious and cultural differences. The potential value of tolerance in Buwun Sejati village life was then written by the online media Mandalika Post in a news story. The focus of the research is to find out the branding of the Buwun Sejati tourist village as a tolerance tourism village through the Mandalika Post online media coverage. This study was designed in a qualitative descriptive with data collection techniques of observation, interviews and documentation. The results showed that in carrying out a branding of Buwun Sejati tourism village as a tolerance tourism village, it was actually quite unique compared to other tourist village branding. The residents of Buwun Sejati village do not need to make major changes in community life in their village, in an effort to attract tourist visits. because the life of the people who live side by side in the midst of religious, ethnic and cultural differences, it becomes the potential advantage of the village to become a tourist attraction, but what needs to be done is to inform the potential of Buwun Sejati village as a tourism village of tolerance to the wider audience so that the existence and unique attraction of Buwun village Indeed, it is known by the wider community so that it can attract tourist visits. The branding of the Buwun Sejati tourist village as a tolerance tourism village was carried out by Mandalika Post in an online news story. In an effort to branding news writing using a 5 W + 1 H writing structure, namely What, What, Where, When, Why, and How. The structure of the news writing is done so that the wider community or readers can obtain clear information about the tolerance tourism village of Buwun Sejati. Keywords: Branding; Tourism Village; News; Online Media.